2016
DOI: 10.1016/j.corsci.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced corrosion of absorbable magnesium alloy: In-situ and real-time electrochemical study

Abstract: An in-situ and real-time electrochemical study in a vascular bioreactor was designed to analyze corrosion mechanism of magnesium alloy (MgZnCa) under mimetic hydrodynamic conditions. Effect of hydrodynamics on corrosion kinetics, types, rates and products was analyzed. Flow-induced shear stress (FISS) accelerated mass and electron transfer, leading to an increase in uniform and localized corrosions. FISS increased the thickness of uniform corrosion layer, but filiform corrosion decreased this layer resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 56 publications
0
28
0
5
Order By: Relevance
“…Three time constants can be assigned for the EIS plots of all the samples. For Zn and Mg, they consist of two capacitive loops at high and medium frequencies and one inductive loop at low frequencies [42,43], while for Fe, two capacitive loops at high and low frequencies can only be identified, probably because the scanning frequency range does not suffice to cover the slower steps. Therefore, two types of equivalent circuits models (embedded in each Nyquist plot) were applied to decode their components.…”
Section: Transient Electrochemical Corrosion Behaviormentioning
confidence: 98%
“…Three time constants can be assigned for the EIS plots of all the samples. For Zn and Mg, they consist of two capacitive loops at high and medium frequencies and one inductive loop at low frequencies [42,43], while for Fe, two capacitive loops at high and low frequencies can only be identified, probably because the scanning frequency range does not suffice to cover the slower steps. Therefore, two types of equivalent circuits models (embedded in each Nyquist plot) were applied to decode their components.…”
Section: Transient Electrochemical Corrosion Behaviormentioning
confidence: 98%
“…In an in-situ experiment, the corrosion of an Mg alloy was electrochemically monitored (real time) in a vascular bioreactor. It was observed that the flow-induced shear stress caused faster mass and electron transfer of the alloy during corrosion [39]. These two examples suggest that certain in-vivo conditions affect the corrosion behavior of absorbable metals and indicate the importance of correlating the results obtained by in-vitro experiments with those of in-vivo tests.…”
Section: Introductionmentioning
confidence: 93%
“…Over the past five years, several systems have been developed to study the behavior of absorbable metals during corrosion in realtime. By developing a set-up composed of a vascular bioreactor (with circulation of simulated body fluid to simulate the dynamic in-vivo condition) and an electrochemical cell (attached to a potentiostat), (Figure 6b) Wang et al [39] investigated the corrosion of a Mg alloy in-situ. Another electrochemical-based system was developed to monitor the real-time corrosion of Mg, namely the corrosion characterization system [67].…”
Section: Electrochemical-based Monitoring Systemmentioning
confidence: 99%
“…Additionally, there is always a steep concentration gradient around the degradation interface, that is, alkaline pH is rapidly refreshed by circulating medium. The fresh metal surface and medium replacement promoted degradation [32]. Because of the fast degradation, the part of the Mg that exposed to the lumen fractured at the 3rd day (Fig.…”
Section: Resultsmentioning
confidence: 99%